Challenging diagnosis of Kimura disease in a child with nephrotic syndrome: A case report - Roya Hemayati; Fariba Binesh; Mohammad Pashmchi; Seyyed Mohammad Kazem Mousavi Anary; Mohammad Mohammadi (Clinical Case Reports)
Abstract Kimura disease (KD) is a rare condition with a challenging diagnosis because it may be misdiagnosed and not differentiated from other disorders. We reported a 13‐year‐old patient who presented with growing neck masses and was hospitalized due to the nephrotic syndrome relapse but was eventually diagnosed with KD.